WHAT HAPPENS TO SWEAR WORDS IN SUBTITLING? A CASE STUDY OF THE FINNISH SUBTITLES OF THE INBETWEENERS - Vainio-Puhju, Vilja (My University, 2020)
This thesis studies the omissions of swear words, the context of the omissions and the possible reasons behind the omissions from the Finnish subtitles of a British television series called The Inbetweeners. The research material of this thesis is collected from the first season of The Inbetweeners, consisting of six episodes. The series can be found in the streaming service Netflix. The material consists of both the original English audio and the Finnish subtitles. After the theory part concerning swear words and translator’s practices of dealing with them, there follows and introduction of those swear words whose omissions will be analyzed in the thesis. The swear words will be divided into two main categories: four-letter words and name-calling words. Lastly, the research material will be analyzed in order to explore possible reasons behind the omissions. The results of the study provide a few possible reasons for the omission of swear words from the Finnish subtitles, main reasons being the constraints of audiovisual translation, the redundancy of swear words in the process of conveying a message to the audience and finally, a common understanding among translators that swear words are stronger in a written form than they are in a spoken form (i.e. their offensiveness is greater in writing), which results in a need to omit swear words from the subtitles. In order to gain more accurate and detailed information on the omission of swear words from subtitles, it would be useful to study the practice of omitting swear words in both a wider and a more detailed scope. It would be crucial to conduct a research on the argument that swear words are stronger when they are in a written form in order to better understand the viewer’s opinions on the strengths of swear words and the effects those opinions have on the viewing experience. This kind of a research would benefit future research on this topic immensely.
Keywords: swear word, swearing, translation, subtitles, The Inbetweeners